2024
DOI: 10.1039/d3ta08079j
|View full text |Cite
|
Sign up to set email alerts
|

Pyridine-induced caused structural reconfiguration forming ultrathin 2D metal–organic frameworks for the oxygen evolution reaction

Yang Liu,
Shuwei Deng,
Shihui Fu
et al.

Abstract: Two-dimensional metal-organic frameworks (2D MOFs) as an ideal prototype material for electrocatalytic oxygen evolution reaction (OER) can expose more metal active sites due to their ultrathin 2D structure. Herein, a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The oxygen evolution reaction (OER) restricts the advancements of technologies that rely on water splitting due to its high activation barrier and consequently its slow kinetics. 1–5 Namely, water electrolysis, electrochemical reduction of carbon dioxide, rechargeable metal–air batteries, and regenerative fuel cells are greatly affected by the slow kinetics of the OER. 6,7 Exploring efficient earth-abundant catalysts for the OER has been a long-time goal.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen evolution reaction (OER) restricts the advancements of technologies that rely on water splitting due to its high activation barrier and consequently its slow kinetics. 1–5 Namely, water electrolysis, electrochemical reduction of carbon dioxide, rechargeable metal–air batteries, and regenerative fuel cells are greatly affected by the slow kinetics of the OER. 6,7 Exploring efficient earth-abundant catalysts for the OER has been a long-time goal.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are constructed by connecting inorganic secondary building units (SBUs) with organic ligands to form an infinitely three-dimensional chemical space, 20–23 which provides a unique platform to design homogeneous active catalytic sites into heterogeneous catalysts due to its permanent open pores. 24–27 Pioneering studies have shown that the immobilization of the cobalt-oxo cubane core (Co 4 O 4 ) into a MOF will stabilize the active sites and prevent them from intermolecular decomposition during OER catalysis. 28 However, MOF materials usually show poor conductivity and stability, which limits their catalytic performance.…”
Section: Introductionmentioning
confidence: 99%